Regulasi Pasar dan Etika Penetapan Harga: Pandangan Klasik dan Kontemporer Para Fuqaha - Prayudi Kumala (Qisth : Jurnal Studi dan Penelitian Hukum Islam, 2025)
The concept of pricing in Islam is in accordance with maqasid sharia that aims with benefit. In determining the price of buikan only based on demand and supply. However, it must pay attention to aspects of justice, honesty, and welfare aspects. The market can play an effective role in life on the principle of free competition can apply effectively. The market does not expect intervention from any party, including the state with pricing authority or the private sector with monopolistic or other. The type of research in this paper is to use descriptive analysis with a comparative causal approach, which is a research that focuses on actual old causal comparisons by compiling, analyzing, and interpreting. The method of this writing is library research (liberary reseach), namely writing taken by theoretical basic research in collecting data from the library.